The Meaning and Contemporary Relevance of Establishing Social Order in Society in the Light of Islamic Teachings - Saira Razaque; Dr Rab Nawaz (Journal of Religion and Society, 2025)
This research paper explores the concept of establishing social order in light of Islamic teachings and examines its relevance in the contemporary world. Islam, being a comprehensive code of life, provides guidance not only for individual conduct but also for collective and societal matters. The Qur’an and Sunnah lay down fundamental principles such as justice, equality, consultation (shura), rule of law, and the fulfillment of mutual rights and responsibilities, which are essential for the formation of a peaceful and organized society. The study highlights the practical model of the Islamic state of Madinah established by the Prophet Muhammad (peace be upon him) in the light of basic Islamic Teaching, where justice prevailed, minority rights were protected, and a balanced socio-political structure was introduced. In the present age, where societies face challenges like corruption, inequality, social unrest, and moral decline, Islamic principles offer viable and sustainable solutions for good governance and social harmony. The findings of this research affirm that the Islamic system of social order is not confined to religious societies but holds universal appeal. Its ethical and legal framework can be adapted to address modern governance issues, providing a path toward a just, equitable, and peaceful global society. Integrating Islamic and contemporary perspectives can thus contribute significantly to the development of a balanced and inclusive socio-political system. Keywords: Meaning. Contemporary Significance. Establishing Order. Islamic Teachings